Spatio-temporal variability of desert dust storms in Eastern Mediterranean (Crete, Cyprus, Israel) between 2006 and 2017 using a uniform methodology - Achilleos, Souzana; Mouzourides, Petros; Kalivitis, Nikos; Katra, Itzhak; Kloog, Itai; Kouis, Panayiotis; Middleton, Nicos; Mihalopoulos, Nikos; Neophytou, Marina K A; Panayiotou, Andrie G.; Papatheodorou, Stefania; Savvides, Chrysanthos; et al. (My University, 2020)
The characteristics of desert dust storms (DDS) have been shown to change in response to climate change and land use. There is limited information on the frequency and intensity of DDS over the last decade at a regional scale in the Eastern Mediterranean. An algorithm based on daily ground measurements (PM10, particulate matter ≤10 μm), satellite products (dust aerosol optical depth) and meteorological parameters, was used to identify dust intrusions for three Eastern Mediterranean locations (Crete-Greece, Cyprus, and Israel) between 2006 and 2017. Days with 24-hr average PM10 concentration above ~30 μg/m3 were found to be a significant indicator of DDS for the background sites of Cyprus and Crete. Higher thresholds were found for Israel depending on the season (fall and spring: PM10 > 70 μg/m3, winter and summer: PM10 > 90 μg/m3). We observed a high variability in the frequency and intensity of DDS during the last decade, characterized by a steady trend with sporadic peaks. The years with the highest DDS frequency were not necessarily the years with the most intense episodes. Specifically, the highest dust frequency was observed in 2010 at all three locations, but the highest annual median dust-PM10 level was observed in 2012 in Crete (55.8 μg/m3) and Israel (137.4 μg/m3), and in 2010 in Cyprus (45.3 μg/m3). Crete and Cyprus experienced the same most intense event in 2006, with 24 h-PM10 average of 705.7 μg/m3 and 1254.6 μg/m3, respectively, which originated from Sahara desert. The highest 24 h-PM10 average concentration for Israel was observed in 2010 (3210.9 μg/m3) during a three-day Saharan dust episode. However, a sub-analysis for Cyprus (years 2000-2017) suggests a change in DDS seasonality pattern, intensity, and desert of origin. For more robust conclusions on DDS trends in relation to climate change, future work needs to study data over several decades from different locations.
Keywords: Dust storms; AOD; MENA region; PM(10); Trend